Investigating metabolite channelling in primary plant metabolism - Beard, K (2013)
The tricarboxylic acid (TCA) cycle is one of the central pathways in respiration and also plays an important role in a variety of metabolic processes including the synthesis of secondary metabolites and the provision of carbon skeletons for ammonium assimilation and amino acid biosynthesis. Effective regulation of these multiple demands on the TCA cycle is likely to be very important for plant fitness. One way that this regulation could be achieved is through metabolite channelling. This occurs when metabolites are transferred between enzyme active sites without diffusing into the bulk aqueous phase of the cell, and is known to be important in regulating demands in metabolic pathways. Although there is evidence that metabolite channelling exists in animals, there have been no attempts to investigate it in plant. The first aim of this thesis was therefore to investigate whether metabolite channelling exists in the plant TCA cycle. Isotope dilution experiments were developed to investigate metabolite channelling, and were able to show that metabolite channelling was present between certain enzymes of the TCA cycle in both S. tuberosum and A. thaliana mitochondria. The second aim of the thesis was investigate whether metabolite channelling is important in regulating the TCA cycle in plant mitochondria. The pattern of metabolite channelling did not change in mitochondria isolated from the light and the dark, or from mitochondria with increased or decreased TCA cycle rates, but it was not possible to say whether the metabolite channelling altered in a quantitative fashion. Overall the thesis provides the first direct evidence of channelling in the TCA cycle in plants, and further work should help to elucidate what role, if any, it plays.